Preparation And Development Of An Ethylene Vinyl Acetate (Eva) Copolymer Emulsification System For Pour Point Depressant (Ppd) Application - Rosdi, Muhamad Ridhwan Hafiz (2016)
PPD emulsion product is advantageous for use in sub-ambient temperature as it improve the physical handling characteristic compared to traditional product. The preparation of stable EVA copolymer emulsion is critical for the success of production of EVA copolymer emulsion. This study considers the effect of different VA (vinyl acetate) of EVA copolymer in producing the emulsion form as to maintain the emulsion stability. Through the intrinsic viscosity and gel permeation chromatography analysis, the relationship between VA content of EVA copolymer and the flow ability response of an emulsion during emulsification is explored. The result is shown that higher VA content contributes to the instability of the emulsion. Effects VA content were further study by varying the solvent/polymer ratio to observe the flow-response of the emulsion. The results showed that in each series, a higher solvent/polymer ratio produces good flow ability emulsion at 12% and 18% of VA content. Furthermore, these results also revealed that the solubility parameter and VA content show good correlation and that molecular weight has an important influence on the flow ability response of emulsion and pour point reduction. EVA12S8 emulsion exhibited the highest pour point reduction, 12oC at 300 ppm. Subsequently, impact of nonionic emulsifier on emulsion stability was studied as to obtain the optimal loading. Interfacial tensiometer, ZetaSizer Malvern instrument, emulsion stability test, freeze–thaw cycle method, and Brookfield viscometer were employed to investigate emulsion stability. Increasing the emulsifier concentration up to 3% will decrease the interfacial tension in the system efficiently, thus allowing for more efficient droplet break-up during emulsification. This will reduce the particle size, which in turn increased the stability and viscosity of the system. Beyond this loading, the emulsion stability began to decline. Afterward, the effects of different homogenization parameters on emulsion stability were investigated. The emulsion was prepared using paddle agitator and high-shear mixer. Sorbitan monooleate(Span 80) at constant 3% loading as emulsifier. Three parameters were monitored in this section, namely stirring intensity, homogenization temperature and time. The results showed that the optimum homogenization conditions are: stirring intensity, 5000 rpm; homogenization temperature, 80oC and homogenization time, 30 minutes. Exceed these conditions as commonly referred as over-processing; it will impair the emulsion particle size and the emulsion stability.